The Impact of Digitalization on the Process of Informatization of Modern Societies : Socio-Philosophical Analysis - Mukhiddinova Shakhnoza Anvarovna (Indonesian Journal Publisher, 2025)
This article explores the impact of digitalization on the process of informatization in modern societies through a socio-philosophical perspective. The study aims to analyze how the widespread integration of digital technologies reshapes social structures, communication patterns, knowledge production, and human subjectivity. The research employs qualitative philosophical analysis, critical interpretation of contemporary theories, and comparative examination of social transformations driven by digital technologies. The findings indicate that digitalization accelerates informatization by expanding access to information, intensifying social interaction, and creating new digital identities and virtual communities. At the same time, the study reveals emerging challenges such as digital inequality, ethical dilemmas, technological dependence, and the transformation of human agency within algorithm-driven environments. The article concludes that digitalization represents not only a technological shift but also an ontological and cultural transformation that requires the development of digital culture, ethical responsibility, and critical thinking to ensure sustainable and human-centered social development.